Flexible, Flame-Resistant, and Dendrite-Impermeable Gel-Polymer Electrolyte for LiO2/Air Batteries Workable Under Hurdle Conditions - Zou, X.; Lu, Q.; Zhong, Y.; Liao, K.; Zhou, W.; Shao, Zongping (Wiley, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Gel-polymer electrolytes are considered as a promising candidate for replacing the liquid electrolytes to address the safety concerns in Li–O2/air batteries. In this work, by taking advantage of the hydrogen bond between thermoplastic polyurethane and aerogel SiO2in gel polymer, a highly crosslinked quasi-solid electrolyte (FST-GPE) with multifeatures of high ionic conductivity, high mechanical flexibility, favorable flame resistance, and excellent Li dendrite impermeability is developed. The resulting gel-polymer Li–O2/air batteries possess high reaction kinetics and stabilities due to the unique electrode–electrolyte interface and fast O2diffusion in cathode, which can achieve up to 250 discharge–charge cycles (over 1000 h) in oxygen gas. Under ambient air atmosphere, excellent performances are observed for coin-type cells over 20 days and for prototype cells working under extreme bending conditions. Moreover, the FST-GPE electrolyte also exhibits durability to protect against fire, dendritic Li, and H2O attack, demonstrating great potential for the design of practical Li–O2/air batteries.